한국 소아 식품알레르기의 연구 현황과 과제 - 안강모 (Allergy asthma & respiratory disease, 2018)
Food allergy is an immune-mediated adverse reaction that occurs mainly by consumption of food. Some of the children with food allergies have mild symptoms like urticaria and pruritus, while others manifest fatal symptoms like anaphylaxis. Many cases develop in infants and children, and disappear spontaneously over time. The prevalence of food allergy is known to be up to 6% of children and 3%–4% of adults. Growing concern is that prevalence of food allergy seems to be increasing. The prevalence, common allergens and natural course of food allergy vary according to the race, age, eating habits, and unknown factors. In Korea, many researchers have reported regional data on food allergy for comparison with those of foreign countries. Awareness is increasing and food labelling is being established to help people avoid allergenic foods. In the future, monitoring of prevalence and common food allergens at regular intervals is needed to make appropriate policies for children with food allergy. There are still lack of data on pathogenesis, natural course and clinical trials of immunotherapy in Korean children. In addition, it is necessary to form a consensus on primary prevention of food allergy by early exposure to allergenic foods. Further regional studies should be performed to expand our understanding of food allergy and to lead to proper management for Korean children with food allergy. KCI Citation Count: 2